Probability Distribution of ADAS Metal Dampers in R.C. Buildings Using Nonlinear Analysis: التوزيع الاحتمالي لمخمدات معدنية من نوع ADAS في المباني البيتونية المسلحة باستخدام التحليل اللاخطي - Hala Tawfek Hasan, Khaled Al-Homsi (Journal of engineering sciences and information technology, 2021)
This study discusses the effect of metallic yielding dampers (ADAS) on the behavior of reinforcement concrete buildings when exposed to seismic shocks. The objective of the study is to reduce the negative impacts on the main structural elements (plastic, fall) by using the technique of metallic dampers. The method of metallic dampers is one of the modern ways based on the principle of dissipating the resulting energy from the seismic shock and reducing the needed energy in the main structural elements of the building to keep it in a flexible state. This technique also provides a controlling mechanism for story displacement, the handling of the soft story mechanic and the torsion mechanic of the buildings. In this study, the effect of the addition of ADAS dampers on the construction behavior was observed in terms of (building period, base shear, roof displacement, roof acceleration, story displacement, dissipative energy). Based on the preceding, this study will give the possibility of predicting the behavior of the building when using ADAS metal dampers in the reinforced concrete structures with their distribution methods.